1998
DOI: 10.1091/mbc.9.7.1919
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Contraction of the Stress Fiber

Abstract: Stress fibers were isolated from cultured human foreskin fibroblasts and bovine endothelial cells, and their contraction was demonstrated in vitro. Cells in culture dishes were first treated with a low-ionic-strength extraction solution and then further extracted using detergents. With gentle washes by pipetting, the nucleus and the apical part of cells were removed. The material on the culture dish was scraped, and the freed material was forced through a hypodermic needle and fractionated by sucrose gradient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
206
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(221 citation statements)
references
References 46 publications
14
206
1
Order By: Relevance
“…Isometrically stressed lattices are a more appropriate model of myofibroblast-populated granulation tissue during wound contraction compared with mechanically unloaded floating lattices (Grinnell, 1994). Isometric tension has been shown to be important for the development of myofibroblastic contractile features such as stress fibers (Burridge, 1981;Tomasek et al, 1992;Katoh et al, 1998;Grinnell et al, 1999a) and ␣-SMA expression in collagen lattices (Arora et al, 1999b). To test whether individual ␣-SMA-positive fibroblasts contract more efficiently than ␣-SMA-negative cells under identical conditions, we used a modification of the wrinkling silicone elastomer assay, originally developed by Harris et al (1980), which is particularly useful in order to visualize overall cell contractile forces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isometrically stressed lattices are a more appropriate model of myofibroblast-populated granulation tissue during wound contraction compared with mechanically unloaded floating lattices (Grinnell, 1994). Isometric tension has been shown to be important for the development of myofibroblastic contractile features such as stress fibers (Burridge, 1981;Tomasek et al, 1992;Katoh et al, 1998;Grinnell et al, 1999a) and ␣-SMA expression in collagen lattices (Arora et al, 1999b). To test whether individual ␣-SMA-positive fibroblasts contract more efficiently than ␣-SMA-negative cells under identical conditions, we used a modification of the wrinkling silicone elastomer assay, originally developed by Harris et al (1980), which is particularly useful in order to visualize overall cell contractile forces.…”
Section: Discussionmentioning
confidence: 99%
“…Because wound contraction takes place when de novo expressed ␣-SMA is incorporated in stress fibers (Darby et al, 1990), it has been suggested that this actin isoform plays an important role in granulation tissue contraction (for review see Serini and Gabbiani, 1999). Although stress fibers have been proposed to function as contractile organelles (Burridge, 1981;Katoh et al, 1998) and their presence has been correlated with the production of isometric tension (Harris et al, 1981), at present direct evidence of a functional role of ␣-SMA in fibroblast contraction is lacking. Here, we have used several in vitro models and approaches in order to test the possible correlation between the expression of ␣-SMA and the contractile activity of fibroblastic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Previous efforts to characterise the tensile behaviour of SFs have relied on isolation/extraction of individual SFs from the cell, followed by tensile testing [29]. It is important to note that isolated/extracted SFs behave as a passive material [30], neglecting the critically important features of active myosin induced cross-bridge cycling and remodelling.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclei were isolated from the cultured ECs with a chemical treatment previously reported (Katoh et al, 1998). Briefly, the confluent cells were washed with PBS (Dulbecco's phosphate-buffered saline without Ca 2+ or Mg 2+ , Wako, Osaka, Japan) and treated with an ice-cold low-ionic-strength extraction solution consisting of 2.5 mM triethanolamine (Wako), 1 µg/ml leupeptin (Wako), and 1 µg/ml pepstatin (Wako) in distilled water for 10 min.…”
Section: Isolation Of Nucleusmentioning
confidence: 99%